Normal Thymic Size and Low Rate of Infections in Human Donor Milk Fed HIV-Exposed Uninfected Infants from Birth to 18 Months of Age - Dorthe Lisbeth Jeppesen; Annette Kjær Ersbøll; Tine Ursula Hoppe; Susanne Dam Nielsen; Niels Henrik Valerius (International Journal of Pediatrics)
Objective. To evaluate the immune function in HIV-exposed uninfected (HIV-EU) infants fed human donor milk. Methods. Ultrasound-obtained thymic index (Ti), T-lymphocyte subsets, and the number of infections were examined from birth to 18 months of age in 18 HIV-EU infants. The infants were compared to a cohort of 47 term, HIV-unexposed breastfed or formula-fed infants. Results. The thymic size at 12 months of age was not significantly different between the HIV-EU group and the control infants (P=0.56). At 4 months of age, the HIV-EU infants had significantly fewer infections than the control infants (P<0.001). Furthermore, in the control group, the infants exclusively breastfed at 4 months of age had significantly fewer infections at 8 months when compared to age-matched formula-fed infants (P=0.001). Conclusion. HIV-EU infants fed human donor milk have normal growth of thymus and contract fewer infections than other healthy infants. This finding along with fewer infections in exclusively breastfed infants compared to formula-fed infants supports the beneficial effect of human milk on the immune system. We suggest, when breastfeeding is not possible, that providing human donor milk to vulnerable groups of infants will be beneficial for their maturing immune system.